Retrovirology highlights a quarter century of HTLV-I research - Jeang, Kuan-Teh (BioMed Central, 2005)
In 1977, Takatsuki and co-workers described in Japan a human malignant disease termed adult T-cell leukemia (ATL). Three years later, in 1980, Gallo and colleagues reported the identification of the first human retrovirus, human T-cell leukemia virus type I (HTLV-I), in a patient with cutaneous T-cell lymphoma. This month, Retrovirology commemorates these two land mark findings by publishing separate personal recollections by Takatsuki and Gallo respectively on the discovery of ATL and HTLV.